SOCIAL MEDIA ANALYSIS ON MALAY POLITICAL PARTIES IN MALAYSIA: STUDY ON THE ISSUES AND COMMENTS FACEBOOK - Azahar Kasim; Hasniza Kamarul Zaman, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Social media is very important to disseminate and share information related to political issues to media users. Social media also provides space for media users to comment on political issues. Almost all political parties have their own 'page', as well as the candidates who are contesting, in addition to the content of the manifesto debate between the parties as well as the emotions of supporters and voters are uploaded on Facebook. This study identified the frequency, framing of issues and comments on the four Facebook of political parties. This study is to identify issues of common concern in Facebook Malay political parties and comments by Facebook users on the progress of the administration by the National Alliance government under the leadership of Tan Sri Muhyiddin Yassin. This study used qualitative methods to retrieve data from Facebook Malay political parties such as UMNO, PKR, PAS and BERSATU. Data collected from four political parties’ Malay Facebook starting 1 September 2020 to 31 December 2020. The researchers use Framing Theory to identify the issues that are discussed in social media. The analysis will be made according to the amount of frequency, type of issue, and form of comments discussed through the narrative approach. Based on data collected over the past four months, researchers found that the whole issue is being discussed by UMNO of 285, total 147 PAS, PKR as much as 122 and as many as 21 BERSATU while the issues discussed in the official Facebook account of Malay political party is criticism, elections, COVID-19, political, economic, social, governmental, educational and religious. The most discussed issue is political issues. As for the comment frequency trend, the satirical politeness form strategy was the highest involving comments on the four Facebook political parties.